2018
DOI: 10.1261/rna.064477.117
|View full text |Cite
|
Sign up to set email alerts
|

The S. pombe mitochondrial transcriptome

Abstract: Mitochondrial gene expression is largely controlled through post-transcriptional processes including mitochondrial RNA (mt-RNA) processing, modification, decay, and quality control. Defective mitochondrial gene expression results in mitochondrial oxidative phosphorylation (OXPHOS) deficiency and has been implicated in human disease. To fully understand mitochondrial transcription and RNA processing, we performed RNA-seq analyses of mt-RNAs from the fission yeast RNA-seq analyses show that the abundance of mt-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Results of software-based annotation were verified by manual inspection. The annotations of mt-tRNAArg(UCU) and mt-tRNAGlu(UUC) were revised according to the recently published S. pombe mitochondrial transcriptome analysis (the starting and ending positions of the former were shifted upstream for one nucleotide and six nucleotides, respectively, and the ending position of the latter was shifted downstream for one nucleotide) (Shang et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Results of software-based annotation were verified by manual inspection. The annotations of mt-tRNAArg(UCU) and mt-tRNAGlu(UUC) were revised according to the recently published S. pombe mitochondrial transcriptome analysis (the starting and ending positions of the former were shifted upstream for one nucleotide and six nucleotides, respectively, and the ending position of the latter was shifted downstream for one nucleotide) (Shang et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The RNase T2 family is conserved in almost all eukaryotes so far analyzed, with the exception of trypanosomes and Schizosaccharomyces pombe (Shang et al, 2018;Fricker et al, 2019) and is also found in a large number of bacteria and several viruses. In most nonplant organisms, only one gene belonging to this family is found in each genome (Hillwig et al, 2009;Ambrosio et al, 2014); however, in plants, the RNase T2 protein repertoire has expanded, and individual proteins have been adapted for a variety of functions.…”
Section: Secretory Ribonucleasesmentioning
confidence: 99%
“…Results of software-based annotation were verified by manual inspection. The annotations of mt-tRNAArg(UCU) and mt-tRNAGlu(UUC) were revised according to the recently published S. pombe mitochondrial transcriptome analysis (the starting and ending positions of the former were shifted upstream for one nucleotide and six nucleotides, respectively, and the ending position of the latter was shifted downstream for one nucleotide) (Shang et al 2018). The 69 types of mitogenomes (MT1-MT69) together with their annotations have been deposited at GenBank under accession numbers MK618072-MK618140.…”
Section: Mitogenome Annotationmentioning
confidence: 99%